Is the Territorial Autonomy of Vojvodina a Part of the Constitutional Identity of the Republic of Serbia - Simović, Darko Z (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The Republic of Serbia still does not have a clearly defined constitutional identity. One of the delicate questions from this sphere is whether the territorial autonomy of Vojvodina has become part of the constitutional identity of the Republic of Serbia. An affirmative response to this question can be founded on the belief that territorial autonomy has been a continuous form of decentralization of state for over seven decades. However, if we take into consideration that the territorial autonomy has continually changed and circulated between extreme models; which thereby are not coherent with the theoretical notion of territorial autonomy, it can be concluded that the autonomous province of Vojvodina is a resolute element of the constitutional system of the Republic of Serbia only nominally and only by way of its form, but not its content. Simultaneously, the existing model of territorial autonomy is disputed with criticisms that its level is low, and that its constitutional guarantees are weak and ineffective. These words clearly suggest that the constitutional model of territorial autonomy has yet to finalize its form. Taking into consideration that the territorial autonomy has commonly been a disintegrating factor, in addition to the fact that aside from tradition which is also questionable, there do not exist other convincing factors for the survival of the autonomous province of Vojvodina. The Republic of Serbia should turn toward a different model of territorial decentralization. Key words: constitution, constitutional identity, territorial autonomy, national minorities, Republic of Serbia, Vojvodina.